Mewujudkan Klepu Sejahtera Melalui Aksi Dan Sosial Di Desa Klepu, Donorojo, Pacitan - Reviansyah, Muhammad Adrian Reza; Wisanggeni, Feedayen; Fahriza, Moh. Vickry Nizam; Agustiani, Ririn Dwi; Fauzizah, Vina Rizki; Fahmi, Zurri Maulana; Namira, Dwi Marrulita; Hafizhah, Annisa Kurnia; Hasymi, Cut Amel; Faadihilah, Darell; Susila, M. Endriyo (Universitas Muhammadiyah Yogyakarta, 2025)
Community Service Program – is a must for student in Universitas Muhammadiyah Yogyakarta (UMY), embodying the Tri Dharma (three pillars) of Higher Education: education, research, and community service. Community service program held in Klepu Village, Donorojo District, Pacitan Regency, focuses on stunting prevention as a primary concern for the local community. The key issues addressed include a lack of public awareness regarding balanced nutrition, low rates of exclusive breastfeeding, and limited understanding of the importance of childcare during the first 1000 days of life. This program adopts a Community-Based Participatory Research (CBPR) approach, emphasizing active community involvement in identifying problems, developing solutions, and implementing the program. Implementation methods include Focus Group Discussions (FGD), interactive lectures, simulations, role-playing, and practical demonstrations. Program results indicate an increased understanding among community members about the importance of balanced nutrition and optimal childcare practices for preventing stunting. Furthermore, education for pregnant and breastfeeding mothers has successfully raised awareness of the importance of exclusive breastfeeding and nutritious complementary feeding. The program’s success is supported by culturally relevant approaches and the utilization of existing social structures such as integrated health posts (posyandu) and Family Welfare Movement (PKK) for information dissemination. The synergy between community service team and the community has generated positive impacts that are expected to be sustainable in improving the quality of life for children in Klepu Village. This program also has the potential to serve as a community empowerment model for stunting prevention in other regions. This program has the potential to serve as a model for community empowerment in stunting prevention in other regions. With a culturally based approach, it not only provides practical solutions but also empowers communities to take an active role in safeguarding their children's health. Moving forward, it is essential to continue evaluating and developing the program to reach more communities in need.